Feasibility study of a parabolic cylindrical reflector with wide-band line feed as a compact antenna test range - Steenkamp, J. A. J.(Johannes Andries Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1994.